AN ANALYSIS OF CUSTOMER INTENTION IN USING INTERNET BANKING - Astri Ayu Purwati; Farenc Libara; Muhammad Luthfi Hamzah (International Journal of Economics Development Research (IJEDR), 2020)
The Internet has been widely used in various business fields. The function of the Internet in this modern era is not only for giving information but it also handles banking transactions anytime and anywhere without being limited by time and distance. This study aims to determine and analyze the influence of Perceived Value, Perceived Ease of Use and Perceived Risk to Customer intention to use Internet Banking. The respondents in this study were 100 respondents who visited BCA KCP A.Yani Pekanbaru. The data analysis technique used is multiple linear regression analysis using the t-test and F test for hypothesis testing. The results of this study indicate that not all variables are influential, in Perceived Ease of Use there is no influence, while the variables of Perceived Value and Perceived Risk have an influence on customer intention. The variables of Perceived Value and Perceived Risk have a significant effect, while Perceived Ease of Use variables that do not significantly influence customer intention for using Internet Banking. Keywords : Perceived Value, Perceived Ease of Use, Perceived Risk, Customer Intention